Interpersonal Mindfulness, Social Support, and Subjective Well-Being: A Moderated Mediation Model of Self-Esteem - Azzahrah, Humairah; Rusmana, Nandang; Kharisma Meliala, Aditia (Universitas PGRI Yogyakarta, 2025)
Adolescents' subjective well-being is critical in holistic development, but its determinants must be fully identified. This research investigates the direct and indirect effects of interpersonal mindfulness and social support on adolescent subjective well-being, emphasizing the mediating role of self-esteem. Using a correlational design, purposive sampling was taken from 111 class XI students at the Indonesian Education University Laboratory High School. The validated instruments used include the subjective well-being inventory for high school students, the interpersonal mindfulness scale-short, the student social support scale, and the Rosenberg self-esteem scale. Using JASP path analysis indicates that interpersonal mindfulness and social support do not significantly affect subjective well-being. However, self-esteem shows a substantial direct influence and is a significant mediator between interpersonal mindfulness, social support, and subjective well-being. These findings emphasize the importance of self-esteem in improving adolescents' subjective well-being. Implications of the study include the development of integrative interventions that include mindfulness practices, emphasizing increasing self-esteem and strengthening social support. Education and training programs designed to increase self-esteem, optimize social support, and reduce the negative impact of social media can significantly improve teenagers' subjective well-being. Further research is needed to elaborate on this paradigm's cultural and digital factors.